Need Analysis in Developing Differentiated Assessment Instrument for 7th Grade Junior High School Students Based on Learning Style in Emancipated Curriculum - Ni Komang Ari Yunita Dewi; Luh Gd Rahayu Budiarta; Ida Ayu Made Istri Utami (English Language Education Department, Universitas Majalengka, 2024)
Assessment plays a crucial role in the process of acquiring a foreign language. Assessments are crucial to conduct in order to ascertain enhancements in student learning. The assessment results can serve as a guide for creating impactful learning activities for students. Teachers need to conduct diagnostic assessments as part of the emancipated curriculum in order to ascertain students' characteristics, learning styles, and learning needs. Differentiated instruction was implemented to accommodate the diverse characteristics and learning styles of students. This approach enables students to select learning methods that align with their individual learning style. Implementing differentiated instruction will result in the implementation of differentiated assessment by teachers. Teachers must adapt the assessment process based on the specific instructions for each individual learning style. Therefore, the objective of this research is to conduct a comprehensive analysis of the needs of students and teachers throughout the learning process, with the aim of facilitating the development of differentiated assessment instrument for educators.